Middle School Students' Understanding of Scientific Inquiry: An Investigation of Gender, Grade Level and School Type - HAN TOSUNOĞLU, ÇİĞDEM (DERGIPARK AKAD, 2020)
Scientific inquiry (SI) is one of the most important components in achieving the goal of scientifically literate students. Although it is expressed differently in terms of understanding and skill in curricula, it is obvious that students who have adequate understanding about SI will develop the inquiry skills concurrently. Development of inquiry skills and understanding require a careful planning and implementation of inquiry-based strategies and classroom practices. However, before planning and implementing the inquiry based strategies there is a need for descriptive studies that examines the current state of students' views in order to plan the quality and the content of the practices. Therefore, the aim of this study is to descriptively present the SI views of a total of n = 599 5th, 6th and 7th grade students studying at five schools with different socio-economic states in Turkey. The primary data source of the study is the responses of students gathered from the Views About Scientific Inquiry (VASI), that is developed by Lederman et al. (2014), open-ended questionnaire. The results showed that middle school students' views about all aspects of SI are inadequate. Moreover, in depth analysis showed that majority students who holds informed views about SI are the 6th grade students studying at upper-middle socioeconomic state schools.
Keywords: scientific inquiry; middle school students; scientific literacy; PROFESSIONAL-DEVELOPMENT; SCIENCE; VIEWS; CONCEPTIONS; PROGRAM